DEVELOPMENT OF SCIENCE E-MODULES FOR JUNIOR HIGH SCHOOL CLASS VII BASED ON SCIENCE TECHNOLOGY SOCIETY ON TEMPERATURE AND HEAT MATERIAL - Puteri, Dini Eka; Lestari, Tuti (Department of Science Education, 2025)
Based on the results of the analysis that has been carried out, the data obtained shows that the teaching materials used in schools have not been able to support learning optimally. Students prefer if the teaching materials used are equipped with attractive images, use language that is easy to understand, the material presented is brief, concise, and clear, has work instructions for each activity, is equipped with videos, and practice questions. This type of research is Research and Development (R&D) with the ADDIE development model which consists of the stages of analysis, design, and development. The research instrument consists of a needs analysis questionnaire, validity test questionnaire, and practicality test questionnaire. The data obtained were analyzed using the Likert Scale formula to analyze the results of validity and practicality tests. Based on the results of the research conducted, it was found that the results of the e-module validity test by experts or lecturers were declared very valid with a percentage of 89%, the results of the practicality test by science teachers were declared very practical with a percentage of 94%, the results of the practicality test by students were in the practical category with a percentage of 79%.